Collected works of F. Scott Fitzgerald - Fitzgerald, F. Scott (Ware, Hertfordshire : Wordsworth Editions, 2013)
Francis Scott Key Fitzgerald was an American author of novels and short stories, whose works are the paradigm writings of the Jazz Age, a term he coined himself. He is widely regarded as one of the greatest American writers of the 20th century. Fitzgerald is considered a member of the "Lost Generation" of the 1920s. He finished four novels: This Side of Paradise, The Beautiful and Damned, his most famous, The Great Gatsby and what is now considered his true masterpiece, Tender Is the Night. A fifth, unfinished novel, The Love of the Last Tycoon, was published posthumously. Fitzgerald also wrote many short stories that treat themes of youth and promise along with despair and age.
English language and literature.
Keywords: Fitzgerald, Frances Scott Key, -- 1896-1940; Conduct of life -- Fiction